2014
DOI: 10.1523/jneurosci.0877-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Induces Sarm1-Dependent Cell Death in Sensory Neurons

Abstract: Mitochondrial dysfunction is the underlying cause of many neurological disorders, including peripheral neuropathies. Mitochondria rely on a proton gradient to generate ATP and interfering with electron transport chain function can lead to the deleterious accumulation of reactive oxygen species (ROS). Notably, loss of mitochondrial potential precedes cellular demise in several programmed cell destruction pathways, including axons undergoing Wallerian degeneration. Here, we demonstrate that mitochondrial depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
160
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(179 citation statements)
references
References 56 publications
13
160
0
Order By: Relevance
“…Neurons are especially susceptive to mitochondrial dysfunction. Progressive ROS accumulation in neurons can exacerbate protein aggregation, cell death, and result in onset of neurodegeneration [20]. Recently, it is reported that ROS originated from [4].…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are especially susceptive to mitochondrial dysfunction. Progressive ROS accumulation in neurons can exacerbate protein aggregation, cell death, and result in onset of neurodegeneration [20]. Recently, it is reported that ROS originated from [4].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SARM1 (K597E) expression suppressed axon degeneration and cell death after treatment with carbonyl cyanide 3-chlorophenylhydrazone (CCCP) (Fig. 5 C and D), a mitochondrial toxin that stimulates SARM1-dependent axon degeneration and cell death (7). In contrast, SARM1 (K597E) did not suppress cell death in response to trophic factor withdrawal (Fig.…”
Section: Mutant Sarm1 (K597e) Acts As a Dominant Negative And Blocksmentioning
confidence: 93%
“…Augmenting NAD + biosynthetic pathways protects injured axons from degeneration, suggesting this step is crucial in axonal breakdown (5,6). In addition to local axon degeneration, SARM1 promotes neuronal cell death in response to mitochondrial toxins, oxygen glucose deprivation, and viral infection (7)(8)(9)(10). Activated SARM1 can induce cell death independent of other known programmed cell death programs in a pathway termed sarmoptosis.…”
mentioning
confidence: 99%
“…Several key mitochondrial functions rely on the potential across the mitochondrial inner membrane. Loss of membrane potential is associated with mitochondrial fragmentation and impaired trafficking (4), and can potentially activate cell death pathways (5). To safeguard against these deleterious outcomes, eukaryotic cells have developed quality control mechanisms to monitor the membrane potential of resident mitochondria and selectively eliminate depolarized organelles through mitophagy.…”
mentioning
confidence: 99%